Neonatal Stridor. (25th December 2011) - Daniel, Matija; Cheng, Alan
Abstract : Neonatal stridor is an important condition, in many cases implying an impending disaster with a very compromised airway. It is a sign that has to be considered with the rest of the history and examination findings, and appropriate investigations should then be undertaken to confirm the source of the noise. Neonates with stridor should be managed in a multidisciplinary setting, by clinicians familiar with the intricate physiology of these children, and with access to the multitude of medical and surgical investigative and therapeutic options required to provide first-rate care.